Differentiated Learning Strategies in the Merdeka Curriculum to Improve Student Learning Outcomes - Imala (Global Action and Education for Society, 2025)
Differectiated learning is an approach used in the Merdeka Curriculum to achienve learning objectives. In the process teacher are required to devote a lot of time in preparing teching materials that are tailored to the potential and needs of each student. This study aims to describe the strategy for implementing differentiated learning in the Merdeka Curriculum. This research was conducted at UPT SDN 383 Gresik from Desember 2024 to February 2025. The method used is descriptive qualitative method with data collection techniques in the form of observation, documentation and interviews with principals, teacher and students. Data analysis was carried out through three stages, namely data reduction, data presentation and conclusion drawing. The results show that differentiated learning in the Merdeka Curriculum contributes positifwas able to improve student learning outcomes at UPT SDN 383 Gresik. One of the obstacles experienced by UPT SDN 383 Gresik in implementing the independent curriculum differentiation learning strategy is the lack of time for teacher in preparing learning instruments.